The Impact Of Consumer Boycotts on Brand Loyalty and Market Positioning: Insights From Pro-Israel Product Boycotts in Singkawang City, Indonesia - Ryan Mawendy; Mentari Rachmaniaz Rizki; Nur Afifah; Wenny Pebrianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the impact of consumer boycotts on brand loyalty and market positioning, focusing on pro-Israel product boycotts in Singkawang City, Indonesia. Using a mixed-methods approach, combining quantitative surveys and qualitative interviews, we examine consumer participation in the boycott, its influence on brand loyalty, and the responses of targeted brands. Our findings reveal a significant relationship between boycott participation and decreased loyalty towards boycotted brands, with varying degrees of switching behavior observed. Furthermore, the study highlights the role of socio-cultural factors in shaping consumer responses to boycotts. The research provides valuable insights for brand managers seeking to navigate the challenges of consumer activism and maintain brand loyalty in diverse cultural contexts. Policy implications include the need for brands to engage in transparent communication and demonstrate ethical sourcing practices to mitigate the negative impacts of boycotts.